Evaluation of the adult nervous system in preclinical studies - Butt, Mark (Henry Stewart Talks, 2009)
Brain is a heterogeneous tissue: you must look at many sections, Different toxicants affect different areas, Timing is important but most cell death occurs early (1 to 4 days), Appropriate fixation is crucial, Appropriate staining methods are necessary to detect changes in various cell types (neurons, glial cells)
Archived at 2021/02/25